The Effects of Different Molding Orientations, Highly Accelerated Aging, and Water Absorption on the Flexural Strength of Polyether Ether Ketone (PEEK) Fabricated by Fused Deposition Modeling - Miura Daisuke; Ishida Yoshiki; Shinya Akikazu (MDPI, 2025)
Rising prices are currently a problem in the world. In particular, the abnormal increases in the price of metals, which are often used in dental prosthetics, have increased the burden of dental costs on the public. There is therefore an urgent need to develop prosthetic devices made from materials that are not affected by the global situation and that have excellent biocompatibility and mechanical properties comparable to those of metals. Polyether ether ketone (PEEK) is a promising alternative to metal in dentistry. This study compared the effects of different molding orientations, highly accelerated aging, and water absorption on the flexural strength of PEEK fabricated by fused deposition modeling (FDM) and examined its potential for dental applications. The flexural strength of PEEK stacked at 0 degrees to the molding stage (0 degrees PF), with and without highly accelerated aging, was significantly greater than for the other molding orientations. As with PD, the maximum test load for 0 degrees PF was measured without fracture. PEEK stacked at 45 degrees (45 degrees PF) and 90 degrees (90 degrees PF) to the molding stage easily fractured, as the applied load pulled the stacked layers. No statistically significant difference was found between the flexural strength of 45 degrees PF and 90 degrees PF. The flexural strength decreased under all conditions due to defects in the crystal structure of PEEK caused by highly accelerated aging.